The Diagnostic Utility of Low Neutrophil-to-Lymphocyte Ratio (NLR) as an Indicator of Severity in Adult Dengue Hemorrhagic Fever: A Retrospective Study from Bali - Ayu Sandra Manikasari; I Gusti Ayu Wiradari Tedja; Made Ayu Vita Prianggandanni (Archives of The Medicine and Case Reports, 2026)
Dengue hemorrhagic fever (DHF) remains a critical public health challenge in tropical regions. Unlike bacterial sepsis, where a high neutrophil-to-lymphocyte ratio (NLR) typically indicates severity, viral kinetics in dengue often present differently due to bone marrow suppression. This study evaluates the association between low NLR and disease severity in an adult cohort in Indonesia, aiming to identify a cost-effective marker for risk stratification. A retrospective cross-sectional study was conducted at Wangaya Regional General Hospital, Denpasar, Indonesia, from January to August 2025. We analyzed 92 confirmed adult DHF patients aged 18 years and older. Severity was graded using standard World Health Organization criteria (Grades 1–4). For the purpose of diagnostic performance analysis, severe DHF was defined as Grade 2 (spontaneous bleeding) and Grade 3 (circulatory failure) combined. The correlation between NLR and severity was analyzed using the Spearman rank test. Receiver Operating Characteristic (ROC) analysis determined the optimal cut-off for identifying severe cases. The cohort was predominantly young adults (18–25 years; 47.8%) with a male preponderance (68.5%). The severity distribution included Grade 1 (n=68; 73.9%), Grade 2 (n=21; 22.8%), and Grade 3 (n=3; 3.3%). A significant, moderate inverse correlation was observed between NLR and severity grade (r = -0.347; p < 0.001). Mean NLR decreased progressively from Grade 1 (2.90) to Grade 2 (1.20) and Grade 3 (0.65). ROC analysis for detecting Grade 2 or higher DHF showed an Area Under the Curve (AUC) of 0.82 (95% CI: 0.75–0.89). An NLR cut-off of less than 0.85 yielded a sensitivity of 87.5% and specificity of 72.0%. In conclusion, a low NLR is significantly associated with higher clinical severity in adult DHF. Unlike bacterial infections, a declining NLR below 0.85 serves as a potential marker for identifying patients at risk of bleeding and circulatory compromise in resource-limited settings.